Justice for Eldon ; Measuring up ; Vladi's song [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
The disappearance of Rolito Go, killer of Eldon Maguan after he has been tried, convicted and sentenced to prison. The urgent bills were tax measures calling for more taxes. Interview with Vladimir Barrios about his singing.